The International Whaling Commission—Beyond Whaling - Wright, Andrew J.; Simmonds, Mark P.; Galletti Vernazzani, Barbara (Frontiers in Marine Science, 2016)
Since its establishment in 1946 as the international body intended to manage whaling, the International Whaling Commission (IWC) has expanded its areas of interest to ensure the wider conservation of whales. Several key conservation topics have been taken forward under its auspices including climate change, chemical and noise pollution, marine debris and whale watching. Work on each of these topics at the IWC has grown substantially since the 1990s and remains ongoing. Important developments were the establishment of the Standing Working Group on Environmental Concerns in 1996 and the IWC's Conservation Committee in 2003. Trying to address this diverse set of issues is obviously a challenge, but will be necessary if the long term conservation of cetaceans is to be achieved. Through research, workshops, resolutions and collaboration with other organizations, the IWC has advanced both the understanding of the various issues and the means to manage them with increasing effectiveness. The IWC is likely to remain on the forefront of continuing efforts to address these, and other, conservation concerns and ensure the continued viability of cetacean populations around the globe.